Boron-Containing Non-Flammable Polyurethane Foams. Issue 4 (4th March 2019) - Chmiel, Ewelina; Oliwa, Rafał; Lubczak, Jacek
ABSTRACT: Boron-containing oligoetherol was synthesized from melamine diborate (MDB) with ethylene carbonate. The oligoetherol was then used to obtain polyurethane foams. Additional amount of MDB was also used as additive flame retardant added at the foaming step into foaming composition. Obtained PUFs were non-flammable as demonstrated by vertical and horizontal flaming tests. The products has also high thermal resistance and can be exposed to long term heating at 175°C. Fire properties of the obtained foams were compared with the properties of foams obtained from melamine and propylene carbonate and from MDB and ethylene carbonate. Graphical Abstract: